Assess the Effect of Factors on the Digital Transformation Decision of Businesses in Vietnam (International Journal of Scientific Research and Management (IJSRM), 2023)
The study examines the factors affecting the digital transformation decision of enterprises in Vietnam. Based on behavioral theoretical models and empirical studies on digital transformation, the research team collects and analyses data using Smart PLS software. The research results have shown five positive factors and one negative impact on the intention of enterprises to convert digitally in Vietnam. In addition, the research team conducts an additional assessment of the influence level of the factors through statistics that describe the average value of the element. The outcome of the analysis and evaluation is the foundation for proposing solutions to promote businesses in Vietnam to implement digital transformation